2013
DOI: 10.1128/iai.01129-13
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-10 (IL-10) Inhibits Borrelia burgdorferi-Induced IL-17 Production and Attenuates IL-17-Mediated Lyme Arthritis

Abstract: Previous studies have shown that cells and cytokines associated with interleukin-17 (IL-17)-driven inflammation are involved in the arthritic response to Borrelia burgdorferi infection. Here, we report that IL-17 is a contributing factor in the development of Lyme arthritis and show that its production and histopathological effects are regulated by interleukin-10 (IL-10). Spleen cells obtained from B. burgdorferi-infected, "arthritis-resistant" wild-type C57BL/6 mice produced low levels of IL-17 following stim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 54 publications
0
8
0
1
Order By: Relevance
“…Furthermore, IL-10 is known to be an immunomodulatory and anti-inflammatory cytokine [6,[42][43][44][45].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, IL-10 is known to be an immunomodulatory and anti-inflammatory cytokine [6,[42][43][44][45].…”
Section: Discussionmentioning
confidence: 99%
“…For example, Il10 inhibits Ifng, Il2, and Il17 expression in mice (Hansen et al 2013). By contrast, mice lacking the ability to respond to Il10 present an increase in Ifng and Il17 levels (Gonzalez-Lombana et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The downregulation of IL17 and IFNg expression in 6 h (reduced by approximately fivefold) could be due to an increase in the cytokine levels with an anti-inflammatory activity. For example, Il10 inhibits Ifng, Il2, and Il17 expression in mice (GonzalezLombana et al 2013, Hansen et al 2013.…”
Section: Discussionmentioning
confidence: 99%
“…Mavropoulos et al found that IL-10-producing B cells were impaired in psoriatic arthritis and inversely correlate with IL-17 and IFN- γ production [41]. Hansen et al noted that IL-10 regulated an arthritic IL-17 response following infection with Borrelia burgdorferi [42]. These results indicated that IL-10 could play a significant role in the immune control and regulate the immune responses of the other cytokines during Pneumocystis infection.…”
Section: Discussionmentioning
confidence: 99%